Proses Rehabilitasi Menggunakan Art Therapy bagi Mantan Pengguna Narkoba di Yayasan Sahabat Rekan Sebaya Jakarta - Alfia Primasasti Hanggari; Sokhivah Sokhivah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Narcotics are a frightening scourge on society. Drug use is a pathological behavior that is harmful both to the individual and to society. The widespread use of drugs in Indonesia prompted the government to issue Law No. 35 of 2009 on narcotics, which includes provisions for the rehabilitation of individuals who abuse drugs. Rehabilitation is an effort to enable a person to function normally without addiction to addictive substances. One of the institutions that carries out rehabilitation related to addictive substances is the Sahabat Sehat Rekan Sebaya Jakarta Foundation. This foundation uses art therapy as a rehabilitation method. Therefore, the purpose of this study is to describe the art therapy process as a rehabilitation effort at the foundation. This study uses a descriptive qualitative approach with data collection through interviews, document reviews, and observations using purposive sampling as the informant selection technique. The results of this study show that the rehabilitation process begins with assessment, detoxification, and art therapy, both primary and re-entry, as well as aftercare or monitoring. The results show that rehabilitation using the art therapy method has successfully restored the physical, psychological, and social conditions of former drug users. They are physically fit, not easily tired, and able to control their sleeping hours. Psychologically, they are not anxious and are able to express themselves and their feelings through art, and socially, they began to reconnect with people they had previously cut off due to feelings of shame and lack of confidence.